Multi-state vibronic interactions in the 1,2,3-trifluorobenzene radical cation - Faraji, Shirin; Köppel, Horst (The journal of chemical physics, 2012)
The multi-state and multi-mode vibronic interactions between the five lowest electronic states of the title compound are investigated theoretically by an ab initio quantum dynamical approach. The well-established linear vibronic coupling scheme is adopted, augmented by quadratic coupling terms for the totally symmetric modes. The pertinent system parameters are obtained from outer valence Greens function and equation-of-motion coupled-cluster ab initio calculations. Large-scale quantum dynamical simulations are performed employing a powerful wavepacket propagation scheme. The band shapes and line structures (as far as available) of the experimental photoelectron spectra are well reproduced. Time-dependent electronic populations reveal ultrafast internal conversion processes and allow for important insight into the fluorescence properties of the radical cation. The relation to other fluoro derivatives of the benzene radical cation is discussed.
Gesehen am 28.11.2018